(untitled) (مجلة الفاروق للعلوم, 2025)
This paper examines the translation of modality in English–Arabic legal discourse, with particular reference to Libyan commercial legislation translated into English. Legal language is characterised by precision, obligation, permission, and prohibition, all of which are frequently conveyed through modal expressions such as shall, must, and may in English, and their Arabic equivalents such asيجب and يجوز. The study analyses a range of examples drawn from Libyan commercial laws and resolutions in order to identify the major difficulties encountered in translating modal expressions from Arabic into English. The paper demonstrates that inaccuracies in rendering modality may lead to ambiguity, distortion of legal meaning, and loss of the obligatory or permissive force intended in the source text. Particular attention is given to the translation of deontic modality, especially the legal use of shall, must, and may, and the extent to which translators succeed or fail in conveying these meanings adequately in English. The analysis further highlights the importance of legal competence, contextual understanding, and familiarity with both legal systems in achieving accurate legal translation. The paper concludes that legal translation requires specialised linguistic and legal expertise, and recommends closer collaboration between translators and legal professionals to improve the quality and precision of translated legal texts.